Huang ti nei ching su wên = The Yellow Emperor's classic of internal medicine - Veith, Ilza (University of California Press, 2016)
"The Yellow Emperor's Classic has become a landmark in the history of Chinese civilization. Since 1949, when this first translation of the oldest known document in Chinese medicine was published, traditional medical practice has seen a dynamic revival in China and throughout many countries in the Western world. Elements of this time-honored therapy, including acupuncture and the harmony of human spirit with the natural world, have become part of mainstream medical practice; The Yellow Emperor's Classic provides the historical and philosophical foundation of this practice. Ilza Veith has added an extensive introduction to her monumental translation of this classic work, which is written in the form of a dialogue in which the emperor seeks information from his minister Ch'l-Po on all questions of health and the art of healing."--Jacket.